2016
DOI: 10.1097/bot.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopic Views for a More Accurate Placement of Iliosacral Screws

Abstract: Our findings highlight that misperception can occur using standard inlet and outlet views. We suggest using 2 variations of the inlet views and 3 variations of the outlet views to avoid misperception in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Use of our novel external template to guide K-wire insertion, and subsequent IS screw placement, provided high accuracy, with a shorter operative time and lower radiation exposure than the conventional fluoroscopy-guided technique. Moreover, despite the conventional use of inlet, outlet and lateral fluoroscopy views to guide percutaneous IS insertion, violation of the cortex remains an inherent problem of IS screw implantation [ 18 20 ], with additional fluoroscopic views often required intra-operatively to further improve accuracy. Ozmeric et al [ 19 ] advised that two different inlet views should be used to evaluate the anterior and posterior borders of the sacral body, separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of our novel external template to guide K-wire insertion, and subsequent IS screw placement, provided high accuracy, with a shorter operative time and lower radiation exposure than the conventional fluoroscopy-guided technique. Moreover, despite the conventional use of inlet, outlet and lateral fluoroscopy views to guide percutaneous IS insertion, violation of the cortex remains an inherent problem of IS screw implantation [ 18 20 ], with additional fluoroscopic views often required intra-operatively to further improve accuracy. Ozmeric et al [ 19 ] advised that two different inlet views should be used to evaluate the anterior and posterior borders of the sacral body, separately.…”
Section: Discussionmentioning
confidence: 99%
“…Ozmeric et al [ 19 ] advised that two different inlet views should be used to evaluate the anterior and posterior borders of the sacral body, separately. Kim et al [ 18 ] even suggested using two inlet views (at 25° and 55° from the vertical) and three outlet views (at 25°, 35° and 55° from the vertical) to avoid misperception of the local anatomy. However, any adjustment in the position of the guide wire required in one view should necessarily be reconfirmed on all fluoroscopic views.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the incidence of iatrogenic nerve injuries was 4.8%. More caution should be applied, and careful examination of fluoroscopic images must be performed [ 32 ]. The use of navigation techniques for guidewire placement and intraoperative 3D-image control of the guidewire position are helpful in reducing this complication [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the incidence of iatrogenic nerve injuries was 4.8%. More caution should be applied, and careful examination of uoroscopic images must be performed 26 . The use of navigation techniques for guidewire placement and intraoperative 3D-image control of the guidewire position are helpful in reducing this complication 27,28 .…”
Section: Discussionmentioning
confidence: 99%